TEKNOLOGI PEMETAAN DIGITAL UNTUK PENGEMBANGAN KAWASAN PEMUKIMAN PERUMAHAN ( STUDI KASUS : BUKIT SEMARANG BARU- SEMARANG) - Bambang D Yuwono; Hani’ah Hani’ah (TEKNIK, 2007)
In recent years the requirement of housing have been growing, such growth of population requires theimprovement of quality and quantity. As consequence, the developer which has responsible for this, shouldincrease and apply the enhanced technology. BSB is one of the biggest developer in Central Java hadapplied the digital mapping as solution for developing area.This research is purposed to study and evaluate application of digital mapping for developing housingcoverage area. The study is started from the fact that with using conventional tool of measurement can nothandle the project which need speed, accurate manage data to develop area. .Using digital mappingControlling and maintaining data more easily and Accurate.